Produção de juvenis de carpa capim (Ctenopharyngodon idella) alimentados com capim teosinto (Euchlaena mexicana) e suplementados com ração - Costa, Mário Leão (2006)
This work was accomplished at the Fish Nutrition Laboratory of Universidade Federal de Santa Maria, with the objective of evaluate the development of grass carp juveniles (Ctenopharyngodon idella) fed with teosinte grass (Euchlaena mexicana) and supplied with different feeding rates. Were conduced 2 experiments of 45 days each, between December 2004 to April 2005. Were use 240 juveniles with medium weigh of 10.33 ± 0.33 and 20.15 ± 0.23g in the experiments 1 and 2, respectively. The juveniles were stocked in a water re-use system with 12 boxes of 850 L. In the experiment 1 the tested treatments were: S1% = Teosinte grass + ration (1% of body weight; p.v.) ; S2% = Teosinte grass + ration (2% p.v.); S3% = Teosinte grass + ration (3% p.v.); S4% = Teosinte grass + ration (4% p.v.). In the experiment 2 the treatments were: C = Only teosinte grass; SD = Teosinte grass + ration daily (3% p.v.); SA = Teosinte grass + ration each 2 days (3% p.v.); R = Only ration (3% p.v.). In the experiment 1, a linear increase of medium weight was observed as it increased the supply level (ŷ =12,973733 + 2,148043x, r2=0,83), however didn't significant difference among the treatments S3 and S4%. The best specific growth rate (TCE) was obtained in treatment S4%, with significant difference than other treatments (p <0.05). The carcass yield (RC) didn t significant difference between the tested treatments, however, the filet yield (RF) was higher in the treatments S3 and S4%, not having significant difference between both. In the experiment 2, the variable medium weight, was significant difference (p <0.05) than treatments C, SA and R. Already, the standard length (CP) the highest values were of treatments SA and SD, differing significantly of the other treatments, however, no differed between themselves (p>0.05). The carcass yield (RC) didn't present significant difference between the treatments tested in the experiment 2. The treatments SD, SA and R, didn't significant difference among themselves regarding the filet yield (RF), however there was significant difference among the treatments SD and C. It may be concluded that the growth of grass carp juveniles is positively affected by the association of teosinte grass with ration supply, being necessary a minimum feeding rate (3% p.v.) and the daily supply provides better performance than supply each two days.